The Causality and Threshold Levels of Innovative Work and Entrepreneurial Behaviours of Millennial Farmers: Do Family Characteristics Matter? - Emi Widiyanti; Cahyadin, Malik (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Millennial farmers' innovative and entrepreneurial behaviors have been discussed in the literature. However, the contribution of farmer family characteristics is widely ignored. Purpose: Therefore, this study investigates the causality between millennial farmers' innovative and entrepreneurial behaviors by considering family characteristics in the Boyolali and Klaten regencies.Design/methodology/approach: The estimation methods used are Granger Causality Test and Cross-Section Threshold Regression. Findings/Result: The study findings reveal that innovative work has a one-way causality with entrepreneurial behavior, farmer age has a one-way causality with innovative and entrepreneurial behaviors, and the number of family members has a one-way direction with entrepreneurial behavior. Threshold levels of innovative work and entrepreneurial behaviors were 34 and 71, respectively. In simple terms, the level of entrepreneurial behavior is higher and better than the level of innovative behavior of millennial farmers. The study findings imply that the local government should facilitate and assist the process of improving the innovative and entrepreneurial behaviors of millennial farmers in the regions. Conclusion: This research enhances the literature on innovative work behavior and entrepreneurial behavior by showing their relationship. This research also shows the contribution of family characteristics to innovative work behavior.Originality/value (State of the art): The study of the causality of innovative and entrepreneurial behaviors of millennial farmers by considering family characteristics has yet to be widely conducted. Keywords: innovative behavior, entrepreneurial behavior, millennial farmers, causality, threshold